Pengaruh Uang Saku dan Prilaku Hedonisme Terhadap Risiko Utang Dikalangan Mahasiswa Manajemen 2021 Universitas Buana Perjuangan Karawang - Elsa Laila Listiawati; Ujang Suherman; Rengga Madya Pranata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of pocket money and hedonistic behavior on debt risk among students of the Management Study Program, Universitas Buana Perjuangan Karawang, class of 2021. The method used in this study is quantitative with a quantitative descriptive. The population in this study amounted to 412 students, with a sample of 80 students selected using the simple random sampling method. Data were collected through online questionnaires and analyzed using descriptive statistics, classical assumption tests, and hypothesis tests. The results of the study show that the pocket money variable does not have a significant effect on debt risk. This indicates that the amount of pocket money students receive, both large and small, does not directly affect their decision to go into debt, because it is more influenced by how students manage their money. Conversely, hedonistic behavior has a significant influence on student debt risk, encouraging students to consume excessively for personal pleasure without considering financial ability, thereby increasing the tendency to go into debt as a way to fulfill this lifestyle. Thus, hedonistic behavior has a dominant role in increasing debt risk among students, especially when it is not accompanied by wise financial management. The R-Square value of 0.511 indicates that 51.1% of the variability of debt risk can be explained by two independent variables, namely pocket money and hedonistic behavior, while the rest is influenced by other factors outside the study model